The Lexicon of Self-Driving Vehicles and the Fuliginous Obscurity of 'Autonomous' Vehicles. (29th June 2021) - Marson, James; Ferris, Katy
Abstract: Self-driving cars, also referred to as connected and autonomous vehicles, are not only in vogue among technology and car enthusiasts (among others) but they have been broadly considered to form a new and disruptive means of transport. The benefits of self-driving cars are replete with stories of inclusivity, safety, environmental benefits, and social connectivity. However, the reality of the words 'self-driving' and 'autonomous' in the designation of this form of transport are not only inadequately defined, they appear to be actively misleading individuals as to the capabilities of the vehicle and the responsibility that they as driver or person behind the wheel have when in use. Tesla is at the forefront of this debate given that it not only sells an option for its vehicles of full self-driving capability, but it also uses terms such as autopilot which, we argue, lead to misunderstandings by the public and may have resulted, directly or indirectly, to fatal car crashes. We conclude this paper with a recommendation that legislative change is enacted through use of an existing international Standard which will provide the definition and guidance that is necessary for the benefit of all stakeholders.